THE EFFECT OF MIXED INPACT AEROBIC GYMNAM ON THE IMPROVEMENT OF PHYSICAL FITNESS FOR HIGH SCHOOL STUDENTS PALEMBANG - Wahyu Nopianto; Muhsana El Cintami Lanos; Arisman (Program Pascasarjana Universitas Negeri Jakarta, 2020)
This study aims to improve the physical fitness of students at SMAN 18 Palembang. This type of research is included in the experimental research category. The sample in this study were 30 female students at SMAN 18 Palembang. Data obtained through the Indonesian Physical Fitness Test (TKJI) in numerical units. While the data analysis used different test techniques (t-test). The results of data analysis show that Mixed Impact Aerobic exercise has a significant effect on improving the Physical Fitness of students at SMAN 18 Palembang where tcount ﹥ t table = 3.58> 1.699.